2015
DOI: 10.1155/2015/129695
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Genetic Polymorphisms in Transcription Factor 7-Like 2 and Peroxisome Proliferator-Activated Receptors-γ2 with Type 2 Diabetes Mellitus and Its Interaction with Obesity Status in Emirati Population

Abstract: Background. Transcription factor 7-like 2 gene (TCF7L2) and peroxisome proliferator-activated receptors-γ2 (PPAR-γ2) have a profound effect on the incidence of type 2 diabetes mellitus (T2DM) and had previously been found to be associated with T2DM risk in various ppopulations. However, studies in the Arab population are inconsistent. We conducted a case control study to confirm the association of variants rs10885409 of TCF7L2 and Pro12Ala (rs1801282) of PPAR-γ2 with risk of T2DM and related complications in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…There was no association detected between this SNP and T2DM. In concordance with our study, PPARγ rs1801282 was not associated with the risk of T2DM in the Emirati population [39]. The frequencies of the PPARγ Pro12Ala genotypes were 91.9% for C/C, 8.1% for C/G and 0% for G/G in the Emirati population [39], compared to 87.3%, 11.6%, and 1.1%, respectively, in the diabetic group data in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was no association detected between this SNP and T2DM. In concordance with our study, PPARγ rs1801282 was not associated with the risk of T2DM in the Emirati population [39]. The frequencies of the PPARγ Pro12Ala genotypes were 91.9% for C/C, 8.1% for C/G and 0% for G/G in the Emirati population [39], compared to 87.3%, 11.6%, and 1.1%, respectively, in the diabetic group data in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In concordance with our study, PPARγ rs1801282 was not associated with the risk of T2DM in the Emirati population [39]. The frequencies of the PPARγ Pro12Ala genotypes were 91.9% for C/C, 8.1% for C/G and 0% for G/G in the Emirati population [39], compared to 87.3%, 11.6%, and 1.1%, respectively, in the diabetic group data in the present study. Similar to our findings here, recent studies in Iraqi and Egyptian populations reported no significant association in their cohorts with T2DM [40,41].…”
Section: Discussionsupporting
confidence: 90%
“…However, Bener et al [19] suggested that no significant association between the Pro12Ala polymorphism of the PPARG2 gene and T2DM in Qatari’s population. Al-Safar et al [20] also suggested that confirmed that Pro12Ala mutation in PPARG2 is not associated with T2DM risk in this population. In a study for South Africa population, Vergotine et al [21] reported that the Pro12Ala of PPARG2 is significantly associated with insulin resistance and this polymorphism interacts with IRS1 Gly972Arg, to increase the risk of T2DM.…”
Section: Discussionmentioning
confidence: 68%
“…We also found a relation between the Pro12Ala PPAR-γ2 G allele and lower glucose values (adjusted by waist circumference, sex, and age). Most studies showed no association between the polymorphism and glucose levels in other populations, such as Tunisian (adjusted by age and BMI), Cypriot, Egyptian, and Emirati populations [18,58,62,66]. Other studies have reported an association of minor allele with increased insulin [15,16].…”
Section: Discussionmentioning
confidence: 99%